Investigation of the geodesic acoustic mode in EAST H-mode operation using Doppler backscattering systems. (27th July 2018) - Zhou, C.; Liu, A.D.; Liu, Z.Y.; Wang, M.Y.; Xi, F.; Zhang, J.; Ji, J.X.; Fan, H.R.; Shi, T.H.; Liu, H.Q.; Wang, S.X.; Zhuang, G.; et al.
Abstract: The geodesic acoustic mode (GAM) has been observed for the first time in EAST H-mode operation using Doppler backscattering (DBS) systems. The poloidal and toroidal symmetries of the radial electric field ( E r ) fluctuation ( m   =  0 and n   =  0) have also been demonstrated. Using the multichannel DBS system, the GAM frequencies at different radial locations have been investigated, with observations showing that H-mode GAM acts as a radial coherent eigenmode, rather than a continuum of frequencies in L-mode. The intermittency of GAM is observed in both L-mode and H-mode. The interplay between the background density fluctuations and the GAM intensity is revealed. The bicoherence analysis is also used to verify the presence of the nonlinear interaction between the GAM and background turbulence.